"Something that happens at home and stays at home": An exploration of the lived experience of young carers in Western Australia. (19th February 2018) - McDougall, Emma; O'Connor, Moira; Howell, Joel
Abstract: There are approximately 350, 000 young carers in Australia, yet their experience is not well understood. Young carers face adversities and disenfranchisement by being a young person in a caring role, and the role can affect other areas of their lives. We explored the lived experiences of young carers, aged 14–25 years ( N  = 13), from Western Australia through in‐depth semi‐structured interviews. A phenomenological approach was adopted. A thematic analysis of the transcribed interview data revealed four key themes. "Lessons from the experience" articulates the perceived benefits of the role and the themes: "navigating competing demands, " "desire for normalcy" and "lost in the system" capture the struggles and complexities associated with being a young carer. Although there are challenges to being a young carer, it is something that young carers report can be beneficial and something that is done for those they love.